Responses to the Socio-Ecological Crisis: Perceptions of In-Service Teacher - Gunansyah, Ganes; Ariadi, Septi; Budirahayu, Tuti (Journal of Education Reseach and Evaluation, 2022)
The teacher's response to the problem of the socio-ecological crisis becomes important and urgent as an effort to increase teachers' sensitivity, willingness and ability to identify potential and socio-ecological problems that exist in the school environment and the surrounding area.Therefore, this study aims to analyze how teachers participating in in-service teacher training, called Teacher Professional Education (PPG), perceive socio-ecological issues. This study aims to analyze the teacher's perception of the socio-ecological crisis. This study uses a quantitative analysis approach with a survey method. The population in this study were 102 teachers participating in the Teacher Professional Education Program (PPG) primary school teacher training program, with a sample of 96 people. Data collection uses a questionnaire with an electronic google form format. The data analysis technique used descriptive statistics. The research results on teacher perceptions support the inclusion of socio-ecological crisis material in environmental learning in schools and PPG in in-service teacher training positions. In conclusion, although teachers still practice caring and environmentally friendly habits in schools, teachers have paid attention to the importance of critical environmental learning, outdoor learning, collective, and environmental problems in preventing and overcoming socio-ecological. The implication is that teachers are expected to gain many dimensions and critical environmental perspectives in responding to social-ecological problems.